Effect of Using Indirect Mental Training to Learn Football skills - Younus, Ali Qutaiba (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. The research is aiming to reveal effect of using mental training indirectly in learning some basic football skills and to compare in post-test between two research groups to learn some basic football skills among second-grade middle school students. Materials and methods. The researcher used experimental method for its suitability to nature of research. The research community is represented by second-grade middle school students at Al-Furat Intermediate School for Boys for academic year (2024-2025), numbering (95) students distributed among three sections. The research sample consisted of sections (A, B), which were selected by lottery. Thus, the sample number reached (65) students. A number of sample members were excluded due to their lack of equivalence with sample, in addition to excluding students from section (C), who were selected as a sample for stability and exploratory experiments. Thus, final sample number reached (24) students divided into two groups, an experimental and a control group, with (12) students for each group, at a percentage of (25.263%) of original community. The proposed program was distributed by lottery. The educational programs took six weeks to implement, with two educational units per week for each group, each unit lasted 45 minutes. Results. The results obtained reveal significant differences between results of pre- and post-tests for two research groups in learning skills of side throw and ball control, in favor of post-test. attributed to effectiveness of educational programs used and clear impact on learning and developing skills of side throw and ball control in soccer. The players benefited from educational component through explanation and presentation, through instructions and guidance, or through use of educational videos or educational images. These educational methods helped players form a complete understanding of selected skills. Conclusion. Concluded that educational programs implemented on two research groups had a positive impact on learning the side throw and Ball control skills in soccer. The experimental group, which used an indirect mental training program accompanied by skill exercises, outperformed the control group, which used traditional method skill exercises program only.